Content of Human Right to Favorable Environment in Supply Chain Operations - A. P Getman; Y. V Shchokin; Sergey S. Shestopal (International Journal of Supply Chain Management, 2019)
The article explores the history of the development of content and formalization in today's general international law of the norm on the human right to a favorable environment in supply chain. In the study of internationally known UN documents on the protection of the environment (Stockholm Declaration 1972, World Nature Charter 1982, Rio Declaration on Environment and Development 1992, Johannesburg Declaration 2002, etc.) and the analytical reports on this subject (Brundtland Report 1987, the report of Ksentini 1994, the reports of JH Knox presented to the UN Human Rights Council from 2012 to 2017), the authors of the article focused on the development of the process of individualization this right. Particular attention is paid to the analysis of documents adopted by the UN Human Rights Council from 2012 to the present. According to the authors, they allow, first, to give a more precise formulation of this right – as the right to use a safe, clean, healthy and sustainable environment, and, secondly, to assert the formalization of this right as a universal international legal custom.